The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1371/journal.pone.0053329
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Experimental Choroidal Neovascularization by Curcumin in Mice

Abstract: PurposeTo investigate the effects of curcumin on the development of experimental choroidal neovascularization (CNV) with underlying cellular and molecular mechanisms.MethodsC57BL/6N mice were pretreated with intraperitoneal injections of curcumin daily for 3 days prior to laser-induced CNV, and the drug treatments were continued until the end of the study. The CNV area was analyzed by fluorescein-labeled dextran angiography of retinal pigment epithelium (RPE)-choroid flat mounts on day 7 and 14, and CNV leakag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 72 publications
1
15
0
1
Order By: Relevance
“…23, 24 Of note, microglia have a controversial role in light-induced retinopathy. Although others suggested that microglia could remove apoptotic photoreceptors and cell debris in the injured retina and benefit photoreceptor survival, 25, 26 our work 27, 28 and other groups 29, 30 indicated excessive recruitment and activation of microglia could precede photoreceptor degeneration and was associated with proinflammatory and neurotoxic cytokines in the affected regions. A noteworthy fact is that no study has so far focused on the controversial role of microglia in chronic light-induced retinopathy.…”
mentioning
confidence: 60%
“…23, 24 Of note, microglia have a controversial role in light-induced retinopathy. Although others suggested that microglia could remove apoptotic photoreceptors and cell debris in the injured retina and benefit photoreceptor survival, 25, 26 our work 27, 28 and other groups 29, 30 indicated excessive recruitment and activation of microglia could precede photoreceptor degeneration and was associated with proinflammatory and neurotoxic cytokines in the affected regions. A noteworthy fact is that no study has so far focused on the controversial role of microglia in chronic light-induced retinopathy.…”
mentioning
confidence: 60%
“…These chemokines, by participating in the recruitment of macrophages, spread the degeneration to the retina (Rutar & Provis, ). The overexpression of TNF‐α, VEGF, and IL‐1β along with increased density of macrophages has been shown in excised choroidal neovascular membranes of AMD patients, as well as in laser‐induced CNV (Grossniklaus et al, ; Sheridan et al, ; Xie et al, ; Zou, Xu, & Chiou, ). These molecules may promote angiogenesis (Lavalette et al, ; Yang, Wang, Qian, Zhang, & Huang, ) and vascular hyperpermeability (Clermont et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the drug-delivery of curcumin is mostly gavage [25], oral [60], or by intraperitoneal injection [61], and rarely by intravitreal injection [31], we chose intravitreal injection to achieve the effective local concentration rapidly. In addition, intravitreal injection can be used to distinguish between the treated and untreated eye of a mouse [62-66].…”
Section: Discussionmentioning
confidence: 99%